DIETARY PRACTICES AND PHYSICAL ACTIVITY PERFORMED BY ADOLESCENT IN SELECTED DISTRICTS OF INDIA - Bachani, D; Sogarwal, R; Shukla, S K; Shelat, T; Gupta, S (Indian Journal of Community Health, 2013)
Objectives: The present study assesses the dietary practices and physical activity performed by adolescent in selected districts of India. Also, an attempt was made to correlate key indicators of dietary practices and physical activity with Body Mass Index (BMI). Methodology: The study was carried out between July and December 2011 covering adolescent studying in 8 to 10 standard using WHO recommended STEPS method in 5 districts of Uttrakhand, Maharashtra, Kerala, Madhya Pradesh and Andhra Pradesh of India. In each district, 6 schools (4 rural, 2 urban; 5 Government, 1 Private) were selected through stratified random sampling method. Results: Study revealed that only 8.8% boys and 9.2% girls had good scores both for healthy diet and physical activity. On the other hand 25.2% boys and 24.7% girls had poor scores in both the parameters. Overall nearly 84% adolescents were within normal range of BMI. It was observed that 8.8% boys and 9.2% girls had good index for diet and physical activity. On the other hand 25.2% boys and 24.7% girls had poor index for diet as well as physical activity. Conclusions: Unhealthy diet are consumed quite often, hence steps need to be taken to modify lifestyle that include educating children by teachers, making available healthy and traditional food and high taxation on unhealthy foods, subsidy on fruits and vegetables. Physical activity periods should be re-emphasized and taken seriously by students and teachers.